(untitled) (Journal of Special Education and Rehabilitation, 2014)
Students with intellectual disabilities have difficulties establishing and sustaining relationships with their friends. Some professionals believe that deficit in theory of mind tasks causes these difficulties for the children. The purpose of this study is to investigate the effectiveness of theory of mind training in terms of improving the sociability of students with intellectual disability. The method used for this study was an experimental one, consisted of pre-test and a post-test with a control group. Thirty male and thirty female students with intellectual disabilities from two different primary schools were considered in this study. The participants were chosen by the multi-stage cluster sampling method. Two experimental and two control groups were randomly selected from these students; one experimental and one control group for girls and the same for boys. Nine training sessions were designed for the experimental groups while the control groups took part in their daily school program. The results of this study showed that the scores for socialization in the experimental groups were significantly higher than the ones in the control groups (p<0.05). In this study, training theory of mind tasks led to the improvement of socialization skills in students with intellectual disabilities.